Trophic structure of avifauna in east Amazonian forest fragments - Dario, Fabio Rossano (2008)
This study was achieved in two forest fragments located in East-Amazonian, city of Paragominas, State of Pará, Brazil (located at latitude 3º24’S to 3º38’S, longitude 47º12’W to 47º40’W), in October 2007 and March 2008. The main objective of the study is to analyze the groups of birds that were affected by the forest fragmentation and the isolation of these areas, using avifauna as ecological indicator. The method used to register the avifauna specimens was the technique of observations per fixed points, and the areas were calculated through the Shannon-Weaver diversity index (H’=3,7795) and Equitability Index of Pielou (E=0,7854), for each species the Index of Abundance Point (IPA) was calculated. In 48 hours of observations, it was possible to register a total of 123 species of birds, distributed in 36 families, 15 orders and grouped in nine trophic guilds, which insectivores and omnivores are the most abundant.